Dehumanization of civilization in the context of the threat to human values - Kołodziejczyk, Karina (Folia Philosophica, 2005)
The author of the article presents a few authoritative opinions about modern civilization (R. Zubin, M. Rees, J. Joya, J. Bańka). All of the mentioned thinkers hold the view that recent development of civilization glorifies the „cold” values (a phrase coined by Józef Bańka). The author of the article follows this view and claims that the existence of civilization depends on the choice of values. She asserts that in contemporary times the „protected human values”, as called by Bańka, are threatened with disappearance.